Kajian Pendidikan Vokasi dan Kompetensi Ketenagakerjaan - Sawaliyah, Yuniarsih (YASIN, 2022)
The background of this study is an issue that is often reported in various mass media about the gap between employment and education. As well as expectations of the industry, parents and education providers. This research is qualitative research of vocational education and employment competencies for SMK graduates. The study based on several facts of employment experience and the performance of graduate job seekers. The fact is that the implementation of vocational education in Indonesia is relatively not met the expectations of the industry,is product oriented and the vocational education curriculum has not been relevant to the needs of the job market.